Impact of China on Malaysian Economy: Empirical Evidence of Sign-Restricted Structural Vector Autoregression (SVAR) Model - Mohd Azlan Shah Zaidi; Zulkefly Abdul Karim; Zurina Kefeli @ Zulkefli (Asian Academy of Management Journal of Accounting and Finance, 2018)
China has been developing aggressively since its accession into the World Trade Organisation. Consequently, China has become one of the major trading partners to many countries in the world including Malaysia. To what extent China has affected Malaysian economy has been a hot issue facing the economists and practitioners. This paper examines the influence of China on Malaysian economic performances. Using structural vector autoregression (SVAR) methodology that takes into account the effect of other major trading partner countries such as the U.S., Japan and Singapore, the results indicate that different utilisation of foreign country variables to represent external sector in the model brings about different impact on domestic variables. It is shown that the U.S. is particularly important to affect domestic output while China is more important in influencing domestic inflation and the exchange rate, especially with regards to their respective income shocks. In addition, Singapore plays more dominant role in affecting domestic sector when foreign monetary policy shocks are considered. Japan is however more influential in affecting the exchange rate in some other shocks. While China is showing their dominance in the world economy, the study implies that knowing which country exactly affects which domestic variables is very crucial in mitigating the adverse impact of foreign policy change or shocks in the process of transforming Malaysia’s economy toward high income nation in the near future.